The Effect of Team Product to Improve Students’ Creativity in Writing at SMPN 1 Jonggat - Zukhairatunniswah Prayati (Universitas Pendidikan Mandalika, 2020)
This study investigated the effect of team product to improve students’ creativity in writing at the 8th-grade students of SMPN 1 Jonggat, Central Lombok in the academic year 2018/2019. The research was designed as quasi experiment research. The students were divided into the experimental group and control group. The experimental group was treated using the team product method while the control group was subjected to a conventional method. The data were analyzed using descriptive and inferential analysis. The data in this research was taken from the mean scores of students’ achievement and the score percentages. The subject of this research was the 8th-grade students of SMPN 1 Jonggat, which consisted of 54 students. The instruments of this research were tests and questionnaires. The mean score of students’ creativity in the experimental group was 75 and the writing skill was 76. It was higher than the students in the control group. It can be concluded that the team product had a positive effect on students’ writing skills in relation to creativity at SMPN 1 Jonggat.